PENINGKATAN PARTISIPASI PENDIDIKAN MELALUI PROGRAM KELUARGA HARAPAN - Faiz Aminuddin dan Ahmad Thoyib Syir’ah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2016)
Program Keluarga Harapan (PKH) is a program of conditional aid earmarked for Family Very Poor (KSM) in improving the quality of life through education and health. The government launched PKH aid flows Rp. 950,000.00 - Rp. 3,700,000.00/KSM and followed by counseling and evaluation. This study aims to determine the implementation of the CCT in the District Tayu Pati Regency and the implications of the implementation of the CCT to the participation of children's education PKH aid beneficiaries in the district Tayu Pati regency. This study uses field research is descriptive qualitative. The results showed that PKH in District Tayu Pati regency run in accordance with the targets set by the Central UPPKH. UPPKH District of Tayu participate in the improvement of education of children of KSM by the number of face to face over the number 85%. Such participation has implications for life PKH aid beneficiaries include: the establishment of a responsible society, awareness of the importance of education, increased awareness of higher education and the formation of the educated beneficiaries of PKH.